Iterative Frequency-Domain Channel Estimation and Equalization for Ultra-Wideband Systems with Short Cyclic Prefix. (30th June 2010) - Bahçeci Bahçeci, Salim Salim; Koca Koca, Mutlu Mutlu
Abstract : In impulse radio ultra-wideband (IR-UWB) systems where the channel lengths are on the order of a few hundred taps, conventional use of frequency-domain (FD) processing for channel estimation and equalization may not be feasible because the need to add a cyclic prefix (CP) to each block causes a significant reduction in the spectral efficiency. On the other hand, using no or short CP causes the interblock interference (IBI) and thus degradation in the receiver performance. Therefore, in order to utilize FD receiver processing UWB systems without a significant loss in the spectral efficiency and the performance, IBI cancellation mechanisms are needed in both the channel estimation and equalization operations. For this reason, in this paper, we consider the joint FD channel estimation and equalization for IR-UWB systems with short cyclic prefix (CP) and propose a novel iterative receiver employing soft IBI estimation and cancellation within both its FD channel estimator and FD equalizer components. We show by simulation results that the proposed FD receiver attains performances close to that of the full CP case in both line-of-sight (LOS) and non-line-of-sight (NLOS) UWB channels after only a few iterations.